Targeting ultrasound remission in early rheumatoid arthritis: the results of the TaSER study, a randomised clinical trial. Issue 6 (29th March 2016) - Dale, James; Stirling, Anne; Zhang, Ruiqi; Purves, David; Foley, Jonathan; Sambrook, Martin; Conaghan, Philip G; van der Heijde, Désirée; McConnachie, Alex; McInnes, Iain B; Porter, Duncan
Abstract : Objective: To investigate whether an intensive early rheumatoid arthritis (RA) treat-to-target (T2T) strategy could be improved through the use of musculoskeletal ultrasound (MSUS) assessment of disease activity. Methods: 111 newly diagnosed patients with RA or undifferentiated arthritis (symptom duration <1 year) were randomised to strategies that aimed to attain either DAS28-erythrocyte sedimentation rate (ESR)<3.2 (control) or a total power Doppler joint count≤1 during a combined DAS28-ESR/MSUS assessment (intervention). MSUS examination was indicated if: DAS28-ESR<3.2 or DAS28-ESR≥3.2 with two swollen joints. Step-up disease-modifying antirheumatic drug (DMARD) escalation was standardised: methotrexate monotherapy, triple therapy and then etanercept/triple therapy. American College of Rheumatology (ACR) core-set variables were assessed 3 monthly by a metrologist blinded to group allocation. MRI of dominant hand and wrist, and plain radiographs of hands and feet were undertaken at baseline and 18 months for grading by two readers using the Outcome Measures in Rheumatology (OMERACT) Rheumatoid Arthritis MRI Scoring System (RAMRIS) and van der Heijde/Sharp Score, respectively. The coprimary outcomes were mean change from baseline of DAS44 and RAMRIS erosion score. Results: Groups were matched for baseline clinical, demographic and radiographic features. The intervention group received more intensive DMARD therapy. Both groups demonstrated significant improvements in DAS44 (mean change: control −2.58, intervention −2.69; 95% CI difference between groups −0.70 to 0.48; p=0.72). There were no significant between-group differences for any ACR core-set variables, except DAS44 remission after 18 months (control 43%, intervention 66%; p=0.03). There was minimal progression of MRI and radiographic erosions and no difference in imaging outcomes or serious adverse event rates. Conclusions: In early RA, a MSUS-driven T2T strategy led to more intensive treatment, but was not associated with significantly better clinical or imaging outcomes than a DAS28-driven strategy. Trial registration number: NCT00920478.